1996
DOI: 10.1074/jbc.271.11.6050
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin G1 and Cyclin G2 Comprise a New Family of Cyclins with Contrasting Tissue-specific and Cell Cycle-regulated Expression

Abstract: We describe the isolation and characterization of cDNAs encoding full-length human and murine cyclin G1 and a novel human homologue of this cyclin designated cyclin G2. Cyclin G1 is expressed at high levels in skeletal muscle, ovary, and kidney. Following an initial up-regulation from early G 1 to G 1 /S phase, cyclin G1 mRNA is constitutively expressed throughout the cell cycle in T and B cell lines. In contrast, in stimulated peripheral T cells, cyclin G1 mRNA is maximal in early G 1 phase and declines in ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
147
0
10

Year Published

1998
1998
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 147 publications
(170 citation statements)
references
References 71 publications
10
147
0
10
Order By: Relevance
“…We con®rmed that BMP-4 can induce apoptosis in aggregated P19 cells (data not shown). We were interested in determining if cyclin G is a downstream target of BMP-4 for two reasons: (i) as shown above cyclin G shows pro-apoptotic activity in aggregated P19 cells; (ii) it was reported that cyclin G is induced by a related family member, TGF-b (Horne et al, 1996). Therefore, levels of cyclin G protein were examined in aggregated P19 cells after incubation with BMP-4 ( Figure 5).…”
Section: Bmp-4 Induces Cyclin G Expression In Aggregated P19 Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…We con®rmed that BMP-4 can induce apoptosis in aggregated P19 cells (data not shown). We were interested in determining if cyclin G is a downstream target of BMP-4 for two reasons: (i) as shown above cyclin G shows pro-apoptotic activity in aggregated P19 cells; (ii) it was reported that cyclin G is induced by a related family member, TGF-b (Horne et al, 1996). Therefore, levels of cyclin G protein were examined in aggregated P19 cells after incubation with BMP-4 ( Figure 5).…”
Section: Bmp-4 Induces Cyclin G Expression In Aggregated P19 Cellsmentioning
confidence: 99%
“…Although levels of cyclin G RNA remain constant throughout the cell cycle in actively cycling cells, immunohistochemcal studies have indicated that levels of cyclin G protein decrease to undetectable levels during mitosis (Tamura et al, 1993;Horne et al, 1996;Jensen et al, 1998). It has been reported that overexpression of cyclin G promotes cell growth in the RKO colon carcinoma cell line, suggesting a positive role for cyclin G on the cell cycle (Smith et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Human cyclin G2 (CCNG2) belongs to the 'G' family of unconventional cyclins (Bates et al, 1996;Horne et al, 1996). Unlike other cyclins that function to promote cell cycle progression, CCNG2 has not been detected to form complexes with any cyclin-dependent protein kinases.…”
Section: Introductionmentioning
confidence: 99%
“…Despite structural similarities, some cyclins and CDKs are associated with functions not directly linked to cell cycle progression, e.g., transcription and neurite outgrowth [4][5][6]. Cyclin G2, (G2) is an unconventional cyclin [7,8] expressed at modest levels in proliferating cells, peaking during the late S/early G 2 -phase, that is significantly upregulated as cells exit the cell cycle in response to DNA damage and receptor mediated negative signaling in B-lymphocytes [7][8][9]. Recent reports of differential microarray analyses consistently point to G2 upregulation in parallel with cell cycle inhibition during responses to diverse growth inhibitory signals, such as heat shock, oxidative stress, hypoxia and differentiation, further supporting the hypothesis that G2 has cell cycle inhibitory functions [10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the cyclin G1 gene [19,20], the cyclin G2 gene is not a transcriptional target of p53 [7][8][9]21]. Moreover, ectopic cyclin G1 is primarily a nuclear protein, whereas tagged cyclin G2 is largely cytoplasmic [1,21,22].…”
Section: Introductionmentioning
confidence: 99%